2023
DOI: 10.15789/1563-0625-cbs-2752
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbituril-based Supramolecular complexes with platinum compounds influence on expression of CTLA-4 on Regulatory T cells

Abstract: Tumors are a leading pathology in the population. Chemotherapy cannot provide adequately and effectively to cure patients. Some medicine, such as cytostatic, are characterized by a wide range of side effects and resistance of solid tumors to chemotherapy by these medicines. In recent research, the mechanisms of action of cytotoxic agents have been described, and the most appropriate causes of resistance have been suggested. Drug delivery system based on Cucurbit[7]uril (CB[7]) was used to minimize side effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the case of cucurbituril-based systems, it has been demonstrated that CB [7] does not decrease the immunomodulating properties of platinum drugs in vitro [47]. The CB [7]-carboplatin mixture in PBMC-stimulated and non-stimulated cultures significantly reduced the amount and expression of CTLA-4 of FoxP3 + regulatory T cells compared to the control [48]. It has also been shown that the complex of CB [7] with tuftsin, a peptide with immunostimulating and antitumor effects, increases the production of IFN gamma, a cytokine involved in the antitumor Th1 immune response [49].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cucurbituril-based systems, it has been demonstrated that CB [7] does not decrease the immunomodulating properties of platinum drugs in vitro [47]. The CB [7]-carboplatin mixture in PBMC-stimulated and non-stimulated cultures significantly reduced the amount and expression of CTLA-4 of FoxP3 + regulatory T cells compared to the control [48]. It has also been shown that the complex of CB [7] with tuftsin, a peptide with immunostimulating and antitumor effects, increases the production of IFN gamma, a cytokine involved in the antitumor Th1 immune response [49].…”
Section: Discussionmentioning
confidence: 99%